Miss Nelson has a field day - Allard, Harry; Marshall, James, 1942-1992 (Boston [Mass.] : Houghton Mifflin, 1985)
The notorious Miss Swamp reappears at the Horace B. Smedley School, this time to shape up the football team and make them win at least one game.
Elem. School Library Collection, June 2000.
School Library Journal, June 2000.
Booklist, October 2010.
Horn Book, January 1998.
Kirkus Review, August 1997.
3.0
Keywords: Schools -- Fiction; Teachers -- Fiction; Football -- Fiction; School stories